Measurement of arterial transit time and renal blood flow using pseudocontinuous ASL MRI with multiple post‐labeling delays: Feasibility, reproducibility, and variation. Issue 3 (16th January 2017) - Kim, Dong Won; Shim, Woo Hyun; Yoon, Seong Kuk; Oh, Jong Yeong; Kim, Jeong Kon; Jung, Hoesu; Matsuda, Tsuyoshi; Kim, Dongeun
Abstract : Purpose: To evaluate the feasibility, reproducibility, and variation of renal perfusion and arterial transit time (ATT) using pseudocontinuous arterial spin labeling magnetic resonance imaging (PCASL MRI) in healthy volunteers. Materials and Methods: PCASL MRI at 3T was performed in 25 healthy volunteers on two different occasions. The ATT and ATT‐corrected renal blood flow (ATT‐cRBF) were calculated at four different post‐labeling delay points (0.5, 1.0, 1.5, and 2.0 s) and evaluated for each kidney and subject. The intraclass correlation (ICC) and Bland–Altman plot were used to assess the reproducibility of the PCASL MRI technique. The within‐subject coefficient of variance was determined. Results: Results were obtained for 46 kidneys of 23 subjects with a mean age of 38.6 ± 9.8 years and estimated glomerular filtration rate (eGFR) of 89.1 ± 21.2 ml/min/1.73 m 2 . Two subjects failed in the ASL MRI examination. The mean cortical and medullary ATT‐cRBF for the subjects were 215 ± 65 and 81 ± 21 ml/min/100 g, respectively, and the mean cortical and medullary ATT were 1141 ± 262 and 1123 ± 245 msec, correspondingly. The ICC for the cortical ATT‐cRBF was 0.927 and the within‐subject coefficient of variance was 14.4%. The ICCs for the medullary ATT‐cRBF and the cortical and medullary ATT were poor. The Bland–Altman plot for cortical RBF showed good agreement between the two measurements. Conclusion: PCASL MRI is a feasible and reproducible method for measuring renal cortical perfusion. In contrast, ATT for the renal cortex and medulla has poor reproducibility and high variation. Level of Evidence: 2 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2017;46:813–819